THE ADMINISTRATION'S REFRAINMENT FROM EXECUTING JUDGMENTS IN IRAQI LEGISLATION - Assistant Professor, Ph.D. Naji Marmoos Khalaf (International Journal of Business, Law and Political Science, 2026)
Objective: The research addressed the methods and forms of the administration's failure to implement rulings in Iraqi legislation by addressing the forms of the administration's failure to implement administrative rulings, such as laxity or delay in implementation, partial implementation of the ruling, mis implementation, and then explicit refusal to implement. Method: The methods of disrupting implementation were also addressed, such as disrupting the implementation of the ruling by an administrative decision and a regulatory decision. Results: The study concluded that the judicial rulings and decisions issued by administrative courts, after they acquire executive force, become enforceable and become an administrative executive document, according to the executive formula attached to the copy of the ruling. If they are issued against the administrative body, the administrative body must implement the ruling issued against it by taking immediate executive measures. Novelty: However, there are some practices that some administrative bodies may carry out, such as arbitrarily refraining from taking these measures or delaying them, which results in harm resulting from the interruption or loss of benefit, whether it is specific profits or other benefits.